2007
DOI: 10.5188/ijsmer.15.13
|View full text |Cite
|
Sign up to set email alerts
|

Selective Extraction of Precious Metal from Automotive Catalyst Residue by Thiacalix[6]arene Derivatives

Abstract: Two new thiacalix [6] arene (TC6A) derivatives modified at the lower rims, which are TC6A-COOCH3 (1) and TC6A-COOC2H5 (2), respectively, were synthesized. The metal extraction properties of TC4A, TC6A, 1 and 2 from automotive catalyst residue solution containing platinum-group metal cations have been investigated. TC6A shows the highest extraction capability for Pd cation with higher selectivity. On the other hand, 1 shows the remarkable higher extraction ability for Zr cation between metal cations examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…As shown in Figure 7, the absorbance of 2 at 500 nm was [20] . As illustrated in Figure 8, [11] , but they have not yet studied the effect of pH value on the extractability of TC6A. It is interesting that the extract ability of 3 was increased when pH value gets higher, where 87% of the highest extract ability was done.…”
Section: +mentioning
confidence: 97%
See 2 more Smart Citations
“…As shown in Figure 7, the absorbance of 2 at 500 nm was [20] . As illustrated in Figure 8, [11] , but they have not yet studied the effect of pH value on the extractability of TC6A. It is interesting that the extract ability of 3 was increased when pH value gets higher, where 87% of the highest extract ability was done.…”
Section: +mentioning
confidence: 97%
“…The complexation ability of the thiacalix [4] arene(TC [4]A) towards neutral molecules or metal ions has also been investigated [5], [6], [7], [8] . However, to our best knowledge, there are few reports on molecular extraction system including organic and inorganic compounds by modified TC [6]A and TC [6] A itself [9], [10], [11] . It is because that the synthesis of TC [6]A is still hard because the synthetic yield is very low [12] .…”
Section: C[n]mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, development of novel reagents possessing high separation efficiency for PGMs and high stability in acidic media is needed. Many researchers developed new types of sulfur-based extractants for Pd(II) recovery (El-Hefny and Daoud, 2013;Hamada et al, 2013;Kondo et al, 2010;Narita et al, 2008a;Traeger et al, 2012a,b;Yamada et al, 2007). Narita et al (2004Narita et al ( , 2008a reported the selective extraction of Pd(II) with N,N′-dimethyl-N,N′-di-n-octyl-thiodiglycolamide and N,N,N′,N′-tetra-n-octyl-thiodiglycolamide from base metal ions as a function of HCl concentration (Narita et al, 2004(Narita et al, , 2008a.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the separation of PGMs is carried out using commercially available extractants. Although it is well known that these extracting reagents can extract precious metals from waste solutions, examples of selective separation of particular metal ions from various precious metals are scarce (5,6). Therefore, novel reagents, which can effectively separate rare metals, are required.…”
Section: Introductionmentioning
confidence: 99%